KEEFEKTIFAN MEDIA PEMBELAJARAN “NILA” TERHADAP HASIL BELAJAR SISWA KELAS II PADA MATERI NILAI-NILAI PANCASILA - Belinda Revi Junian; Ilmawati Fahmi Imron; Endang Sri Mujiwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Pancasila Education learning in grade 2 of Jegreg Elementary School still uses teacher's books and student's books, making students less active and having difficulty understanding the material on Pancasila values. Based on the results of observations and interviews, out of 25 students only 8 achieved the KKTP score (75). This study aims to determine the effectiveness of using interactive multimedia "NILA" to improve student learning outcomes. This study uses the Research and Development (R&D) method with the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 25 grade II students, with data collected through observation, interviews, and learning outcome tests. The learning media was tested in a limited and extensive manner. The results of the limited trial showed a completion rate of 100%, and the extensive trial was 100%. These results indicate that interactive multimedia "NILA" is very effective in improving student learning outcomes, exceeding the KKTP score, and can be used without the need for improvement.